Pengaruh Suku Bunga Sbi Dan Kurs Dolar - Marpaung, Annaria Magdalena (STIE Kesatuan, 2009)
SBI interest rate is yield of investments in Sertifikat Bank Indonesia (SBI) which is determined by Bank Indonesia. Dollar exchange rate is the relative price of Dollar against Rupiah. Certificates of Bank Indonesia as free risk investment instruments and Dollar exchange rate are consideration factors before investing in the stock market in stocks so that stock prices are influenced by those two variables. This study used the monthly data of SBI interest rates and monthly Dollar exchange rates and it is officially recorded in Bank Indonesia. The monthly closing prices of IHSG were used for stock prices data. This study used data period 2004-2008 and was processed using SPSS 17.0. The study concluded that the SBI interest rates strongly related, negatively affected and significant on stock prices. SBI interest rate related very weak, negatively affected but not significant on dollar exchange rate. Study of other factors that affect the Dollar exchange rate found that the dollar exchange rate is significantly affected by the balance of payments. Dollar exchange rate related, negatively affected and significant on stock prices. SBI interest rate and Dollar exchange rate simultaneously related very srong, negative effected and significant on stock prices.